Large igneous provinces track fluctuations in subaerial exposure of continents across the Archean–Proterozoic transition. (21st April 2022) - Liebmann, Janne; Spencer, Christopher J.; Kirkland, Christopher L.; Ernst, Richard E.
Abstract: Geological observations and numerical models imply that Archean continents were mostly submarine. In contrast, approximately one third of modern earth's surface area consists of subaerial continental crust. To temporally constrain changes in the subaerial exposure of continents, we evaluate the eruptive environment (submarine vs subaerial) of 3.4–2.0 Ga continental large igneous provinces (LIPs). Our results indicate that up until 2.4 Ga LIPs predominantly erupted onto submerged continents. This period of low freeboard was punctuated by local subaerial eruptions at 2.8–2.7 Ga and 2.5 Ga. From 2.4 Ga–2.2 Ga, extensive subaerial continental volcanism is recorded in six different cratons, supporting widespread subaerial continents at this time. An increase in exposed continental crust significantly impacts atmospheric and oceanic geochemical cycles and the supply of nutrients for marine bioproductivity. Thus, the 2.4–2.2 Ga high‐freeboard conditions may have triggered the earliest global glaciation event and the first significant rise of atmospheric oxygen.